Togo : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Modification of Performance Criteria and Augmentation of Access; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Togo. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper discusses key findings of the First Review Under the Poverty Reduction and Growth Facility for Togo. All relevant performance criteria for the first review were met, some by wide margins. Implementation of the structural reform program was satisfactory. Good revenue collection and restrained spending resulted in a large primary surplus in the first half of 2008. A moderate revision to the end-2008 fiscal primary balance target is proposed to reflect the revenue losses and new expenditures resulting from the price shocks and flooding.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet